Insights into the molecular basis of immunosuppression and increasing pathogen infection severity of ammonia toxicity by transcriptome analysis in pacific white shrimp Litopenaeus vannamei. Issue 88 (May 2019) - Lu, Xia; Luan, Sheng; Dai, Ping; Luo, Kun; Chen, Baolong; Cao, Baoxiang; Sun, Li; Yan, Yunjun; Kong, Jie
Abstract: The high concentration of ammonia resulting from intensive culture system and environmental pollution could cause disease occurrence in shrimp, but little information is available on its molecular mechanisms. In this study, we performed comparative transcriptome analysis among WSSV-infected shrimp under ammonia stress (LAV), WSSV-infected shrimp under normal water (LV), and normal shrimp under ammonia stress (LA) groups to identify the key genes and pathways involved in immunosuppression and increasing pathogen infection severity caused by ammonia toxicity in Litopenaeus vannamei . Totally, 526 significantly differential expressed genes (DEGs) were identified in LAV group compared to LV and LA groups, among which 270 genes were lost expressed and 67 genes uniquely expressed in the LAV group. According to the public functional reports for the annotated DEGs, they potentially involved in the following functions: (1) accelerating pathogen adhesion, invasion and multiplication; (2) reducing the ability for pathogen defense and immune response; (3) inhibiting positive regulation of apoptotic and antioxidant defense for host homeostasis; (4) inhibiting transcription and protein transport; (5) and increasing protein methylation and ubiquitination, etc. A total of 13 pathways were obtained mainly involving in this process, which mainly led to the following changes: (1) increasing the immunosuppression, anemia, endocrine dysfunction, neurotoxic effect and neuroinvasion, atherosclerosis and thrombogenesis, blood-brain barrier penetration, thyroid disorder, necrosis, inflammation, and circadian disturbance; (2) reducing the ability of vascular remodeling, angiogenesis, cell survival, migration, apoptosis, and lymph transferred to blood stream; (3) leading to cell hypertrophy, cellular shape changes, and mesangial matrix expansion. The present results firstly supplied molecular mechanisms for the ammonia toxicity inhibiting the immune system and increasing pathogen infection severity in shrimp, which is a prerequisite for better understanding the pathogenesis caused by ammonia toxicity. Highlights: The mechanism of immunosuppression effect of ammonia toxicity by RNA-Seq. DEGs involved in accelerating pathogen adhesion, invasion and multiplication. DEGs involved in reducing the ability of host for pathogen defense and immune response. DEGs involved in increasing histone methylation and ubiquitination in host. The enriched pathways potentially involved in immune defense and apoptosis.